(untitled) (Research, Society and Development, 2022)
Context: Health education is an effective preventive method to support the care needed for a full life. Much care is needed in the elderly, given the vulnerability of this population. Objective: to present the profile of scientific production on Health Education topics related to the elderly population between the years 2017 and 2021. Methodology: A bibliometric review was carried out, with searches on the Web of Science and Scopus databases, using the descriptors Education in health, Education for health and the Elderly, with their results treated by the RStudio software. Results: 345 documents were found, 1328 authors, USA, Spain, UK, China and Brazil were the 5 best countries in the ranking of production of studies, in the ranking of journals, the best was USA, followed by the UK (with 3 positions in the ranking) and Turkey. Among the top 10 research institutions, 9 are universities. The most used descriptor was Health Education. There was an evolution in the age group descriptors from young adults to middle age and an increase of 404.54% in the growth of publications on the subject in the last 5 years. Final considerations: The profile of scientific production is still not very expressive worldwide, given the importance of the topic in the economic and social spheres. Countries with the largest elderly population do not appear in the main rankings of publications. Brazil ranks 5th in the authorial production on the subject. Research funding is primarily at universities. The elderly are still not properly represented by the descriptors.